The features of the story of property of Jews from Kaunas county parishes during Nazi occupation in Lithuania (1941–1944): confiscation and ownership of the immovable property - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2017)
The subject of the research is the history of property of Lithuanian Jews from Kaunas county parishes during the period of occupation by military forces of Nazi Germany (1941–1944). This time period is valued as a period in Lithuanian history, during which the occupational Nazi authorities performed a reform on Jewish property. It is stated in this study that the expression of the Jewish property reform was visible in the activity of the LAF (Lithuanian Activist Front) operated in Berlin as well, this organization used to invite the people of this country to prepare themselves and when appropriate time comes to commence the Jewish property reform, i.e., to take the property into their own hands, while the Jews themselves had to be expelled from Lithuania. It is argued that the expression of this idea, as well as the circumstances that the projects of formation of the Provisional Government of Lithuania were generated by headquarters of the LAF in Berlin, that in the laws on denationalization drafted by the Government, owners of Jewish origin are valued as persons to whom the property nationalized during the Soviet times would not be returned allows assuming that the Provisional Government had chosen the path of the Jewish property reform. The fact that LAF in Berlin and the Provisional Government of Lithuania intended to involve themselves into organizing this reform denies the circumstance that Nazi authorities had had an influence on their activity. It is stated that the fact that during the period under rule of president Antanas Smetona (1927–1940) there were city reform, i.e. Jewish property reform, opponents and supporters, who had not been influenced by a factor of alien authorities, also the factor of opposing activity shown by president A. Smetona towards a reform concerning Jewish property allows assuming that among members of the LAF in Berlin and the Provisional Government of Lithuania there could be persons who opposed and who supported the Jewish property reform. Lithuanian version of this reform did not have any continuity, because the Nazi authorities recognized neither independence announced by the rebels nor the Provisional Government of Lithuania with its policy to be implemented. Due to pressure exerted by the Nazi, both the Provisional Government and the LAF were forced to terminate their activity. It is stated in the article that the Nazi used the Holocaust in order to execute a reform concerning control over Jews property. It is emphasised therein that confiscation of the property of the Jews from Kaunas county is directly linked to the process of establishment of ghettos that took place in the parishes of Kaunas county and started on August the 7th in 1941. Under leadership of Kaunas Circuit Commissar A. Lentzen, who requested and engaged officers from Lithuanian municipalities and police units, in August of 1941 and at the beginning of September of that year, immovable property owned by more than 445 owners Jews and Jewish communities was confiscated. This operation took place in Kaunas county parishes of Aukštoji Panemunė, Babtai, Čekiškė, Garliava, Jonava, Kruonis, Lapės, Pakuonis, Pažaislis, Raudondvaris, Rumšiškės, Seredžius, Vandžiogala, Veliuona, Vilkija and Zapyškis. The property consisted of 620 residential houses, 209 cattle-sheds, 79 storage units, 75 non-residential houses, 58 residential and non-residential houses, 45 grain sheds, 30 wood sheds, 17 barns, 16 extensions, 15 synagogues, 11 equipment sheds, 10 granaries, 4 sheds, 3 shopas, 3 bathhouses, 3 water mills, 2 small houses, 2 cellars, 2 schools, 2 enterprises, 1 shelter, 1 outdoor kitchen and 1 slaughterhouse. Total area of confiscated land parcels – 1 020,9926 ha. Also, 82 vegetable gardens were confiscated (total area of 49 vegetable gardens was 11.65 ha, while that of 31 vegetable gardens – 29683 square metres). It has been established that the part of the value of this property was 4 599 115 rubbles. It is stated in the article, that after this confiscation, the story of immovable property of Jews from Kaunas county parishes goes in direction not related to genocide of Jews and its constituents either. It has been established that a part of immovable property confiscated from Jews in 1941–1942 was handed over and then owned by 254 residents of Kaunas county and 5 offices Altoniškio forestry unit, Board for Highways (Plentų valdyba), Kaunas Food Trade Unit (Kauno maistprekyba), Pažaislio cooperative society and State Economy institution (Valstybės ūkis). This property used to belong to 207 owners of Jew origin, Jewish communities and Chevra Kadisha, an organization of Jewish men and women. The property owned consisted of 132,5 residential houses, 92 cattle-sheds, 33 storage units, 29 grain sheds, 9 barns, 5 granaries, 4 extensions, 4 sheds, 4 wood sheds, 3 bathhouses, 3 equipment sheds, 3 shopas, 2 small houses, 1 outdoor kitchen, 1 synagogue room, as well as 1 garden, 50.5 vegetable gardens (total area of 149 vegetable gardens was 11.65 ha) and 145 land parcels (total area of 141 parcels was 895.3595 ha, the area of another 4 parcels remains unknown).